2023
DOI: 10.1007/s10926-023-10095-6
|View full text |Cite
|
Sign up to set email alerts
|

The Job Leeway Scale: Initial Evaluation of a Self-report Measure of Health-Related Flexibility and Latitude at Work

Abstract: Purpose Evidence suggests that workers manage health-related challenges at work, in part, by using available leeway to perform work differently. The purpose of this study was to evaluate the reliability and validity of the Job Leeway Scale (JLS), a new 18-item self-report questionnaire designed to assess worker perceptions of available flexibility and latitude to manage health-related challenges at work. Methods Workers seeking assistance for workplace difficulties due to chronic medical condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Our third paper, by Dr. William Shaw and colleagues, Organizational Support Factors Associated with Fatigue and Turnover Intention among Workers with Chronic Health Conditions, examines four organizational support factors for workers with chronic health conditions: heath-related leeway, perceived organizational fairness, sense of community at work, and job control (Shaw et al, 2024). As noted, healthrelated leeway refers to the freedom afforded to workers to self-regulate their work behaviors while managing symptom fluctuations (Shaw et al, 2023). Using a sample of workers with various chronic health conditions who participated in a randomized controlled trial of the Manage at Work intervention, the authors found that higher levels of perceived fairness uniquely contribute to lower levels of turnover intentions and higher levels of leeway uniquely contribute to higher levels of fatigue and turnover intentions.…”
Section: Special Issue Contributionsmentioning
confidence: 99%
“…Our third paper, by Dr. William Shaw and colleagues, Organizational Support Factors Associated with Fatigue and Turnover Intention among Workers with Chronic Health Conditions, examines four organizational support factors for workers with chronic health conditions: heath-related leeway, perceived organizational fairness, sense of community at work, and job control (Shaw et al, 2024). As noted, healthrelated leeway refers to the freedom afforded to workers to self-regulate their work behaviors while managing symptom fluctuations (Shaw et al, 2023). Using a sample of workers with various chronic health conditions who participated in a randomized controlled trial of the Manage at Work intervention, the authors found that higher levels of perceived fairness uniquely contribute to lower levels of turnover intentions and higher levels of leeway uniquely contribute to higher levels of fatigue and turnover intentions.…”
Section: Special Issue Contributionsmentioning
confidence: 99%